Influences on organizational purchase: a case study of an automotive industry / Noor Baizura Mat Yusof - Mat Yusof, Noor Baizura (Faculty of Business and Management, 2007)
The goal of the study to analyze the industrial organizational buying behaviour, whereby focusing on automotive industry. This research tries to analyze how the purchase decision making process within an organization is determined by the conditions of purchase situation and also the characteristics of organizational structure. The aim of the research is also to improve the knowledge of buying industrial process in the automotive industry, thus provide a better understanding on the variables that are involved in the buying center of an organization in purchasing decision-making.